Osilasi Dalam Tangki Pendatar (Surge - Tank) Akibat Penutupan Turbin Secara Mendadak - Sangkawati, Sri (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Surge tank in hydro-power generation plant is placed on the transition between conveyance pipe channel and chute pipe. The dimension of surge tank is designed based on water mass oscillation result in minimum hydrodynamic pressure, such that it can determine form, type, and configuration of the tank. The sudden increase in hydrodynamic pressure (positive water hammer) is caused by abrupt decrease in water discharge to the turbine to reduce load to the generator. This positive water hammer is dependent on the discharge and time of closure of the valve. Mathematical equation that describes mass oscillation in the reservoir-pipe channel-surge tank is dynamic and solution can be easily using numerical techniques. This paper demonstrates the water hammer oscillation in a surge tank. The result shares that, 1) when the ratio between surge tank area (As) to the pipe area (AT), As/AT below 5, the maximum increase in water pressure is significant, ii) when the ratio As/AT greater than 5, the increase in water pressure is not significant and tends to have slight differences. Key Words : surge-tank, mass oscillationsPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3916[How to cite: Sangkawati, S., 2005, OsilasiÂ  Dalam Tangki Pendatar (Surge - Tank) Akibat Penutupan Turbin Secara Mendadak, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 122-129]